Experimental infection with Toxocara cati in pigs: migratory pattern and pathological response in early phase - Sommerfelt, Irma Estela (2014)
Experimental inoculations of approximately 100,000 infective Toxocara cati larval eggs were done in twelve pigs. The T. cati eggs used for inoculation were collected from cat's feces. Another group of three pigs served as an uninfected control. Groups of infected pigs were euthanized at seven, 14, 21, and 28 days post-inoculation (dpi). Tissue samples were taken for digestion and histopathology changes in early phase. The number of larvae recovered from the lungs peaked at seven and 14 dpi and were also present at 21, and 28 dpi. Larvae of T. cati were present in the lymph nodes of the small and large intestine at seven, 14, and 28 dpi and at seven, 14, 21, and 28 dpi respectively. In other studied tissues, no larvae or less than one larva per gram was detected. The pathological response observed in the liver and lungs at seven and 14 dpi, showed white spots on the liver surface and areas of consolidation were observed in the lungs. The lungs showed an inflammatory reaction with larvae in center at 28 dpi. In the liver we observed periportal and perilobular hepatitis. The lymph nodes of the intestines displayed eosinophil lymphadenitis with reactive centers containing parasitic forms in some of them. The granulomatous reaction was not observed in any tissues. The role of the other examined tissues had less significance. The relevance of this parasite as an etiological agent that leads to disease in paratenic hosts is evident.